2013
DOI: 10.1002/chem.201302722
|View full text |Cite
|
Sign up to set email alerts
|

Initial Stages in the Formation of Cu2ZnSn(S,Se)4 Nanoparticles

Abstract: In the beginning: Intermediate species generated in the synthesis of Cu2ZnSn(S,Se)4 nanoparticles (see figure) in oleylamine have been identified. The solvent plays a central role in the reaction mechanism, determining the composition of the nanostructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 46 publications
4
39
0
Order By: Relevance
“…As shown in the HRTEM image of Figure b, the polycrystalline nature of the CuCo 2 O 4 film could be determined through these randomly oriented lattice fringes with interplanar distance (inset) corresponding to the d‐spacing of the cubic CuCo 2 O 4 {311} lattice plane. Moreover, the discontinuous SAED ring patterns (Figure c) embedded within large spots were indexed to {400}, {111}, and {220} reflections, further confirming the cubic crystal configuration and polycrystalline nature of the CCO DIW film . At the atomic scale, the elemental distribution of Cu, Co, and O across the nanosheet was obtained via EDS–STEM line mapping (Figure d), which shows the homogeneous existence of three elements.…”
Section: Resultsmentioning
confidence: 65%
“…As shown in the HRTEM image of Figure b, the polycrystalline nature of the CuCo 2 O 4 film could be determined through these randomly oriented lattice fringes with interplanar distance (inset) corresponding to the d‐spacing of the cubic CuCo 2 O 4 {311} lattice plane. Moreover, the discontinuous SAED ring patterns (Figure c) embedded within large spots were indexed to {400}, {111}, and {220} reflections, further confirming the cubic crystal configuration and polycrystalline nature of the CCO DIW film . At the atomic scale, the elemental distribution of Cu, Co, and O across the nanosheet was obtained via EDS–STEM line mapping (Figure d), which shows the homogeneous existence of three elements.…”
Section: Resultsmentioning
confidence: 65%
“…Mostly, the surface atoms on QDs are coordinated with surface ligands, which are indispensable during the QDs synthesis . Recent studies showed that these surface ligands could also affect efficiency during photocatalytic hydrogen evolution.…”
Section: Surface Manipulation Of Qds For Photocatalytic Hydrogen Evolmentioning
confidence: 99%
“…Although this is a two‐step procedure, it allows for more precise control over particle size and metal ratios than the impregnation method described previously, therefore enabling catalyst structure–activity relationships or catalyst‐support interactions to be identified 2. 9, 10 Colloidal thermolytic synthesis can be performed by the “heat up” or “hot injection” approaches 11. 12 In the former case, the reaction mixture is heated, leading to reduction of the precursors at higher temperature, whereas in “hot injection” the cold solution of precursors is injected at higher temperatures into the hot reaction mixture 11.…”
Section: Introductionmentioning
confidence: 99%
“…[2,9,10] Colloidal thermolytic synthesisc an be performed by the "heat up" or "hot injection"a pproaches. [11,12] In the formerc ase, the reaction mixture is heated, leadingt or eduction of the precursors at highert emperature, whereasi n" hot injection"t he cold solution of precursors is injecteda th ighert emperatures into the hot reactionm ixture. [11,12] This solution-phases ynthesis is employedi nt he preparation of aw ider ange of materials, including semiconductors, quantumd ots, mono-a nd multimetallics, magnetic particles and metalo xides, all at the nanoscale and with control over their size, shape and composition.…”
Section: Introductionmentioning
confidence: 99%